Answer:
Step-by-step explanation:
stop cheating lololololol
Answer:
![y = 23.75x + 76.24](https://tex.z-dn.net/?f=y%20%3D%2023.75x%20%20%2B%2076.24)
Step-by-step explanation:
We want to rewrite
![y = 99.99 + 23.75(x - 1)](https://tex.z-dn.net/?f=y%20%3D%2099.99%20%2B%2023.75%28x%20-%201%29)
in the form
![y = ax + b](https://tex.z-dn.net/?f=y%20%3D%20ax%20%2B%20b)
We expand to get:
![y = 99.99 + 23.75x - 23.75](https://tex.z-dn.net/?f=y%20%3D%2099.99%20%2B%2023.75x%20-%2023.75)
Regroup similar terms:
![y = 23.75x - 23.75 + 99.99](https://tex.z-dn.net/?f=y%20%3D%2023.75x%20-%2023.75%20%2B%2099.99)
Simplify:
![y = 23.75x + 76.24](https://tex.z-dn.net/?f=y%20%3D%2023.75x%20%20%2B%2076.24)
This is now of the form
![y = ax + b](https://tex.z-dn.net/?f=y%20%3D%20ax%20%2B%20b)
where a=23.75 and b=76.24
-1/2(x + 2) + 11/2 + x = 3
-1/2x - 1 + 11/2 + x = 3
1/2x + 9/2 = 3
1/2x = 3 - 9/2 = -3/2
x = -3/2 * 2 = -3
x = -3
Answer:
x = 15
Step-by-step explanation:
isolate the variable by dividing each side by the factors that don’t contain the variable